2013
DOI: 10.1007/s00104-012-2430-7
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonektomie

Abstract: Lung cancer is localized in the upper lobes in more than half of the cases. The risk of tumor infiltration of centrally located structures, such as bronchi and vessels are enhanced due to the anatomic topography. Pneumonectomy competes with sleeve resection for the surgical resection of centrally located tumors. The present review deals with the question if pneumonectomy should be considered as an alternative to sleeve resection for the treatment of lung cancer. Primary pneumonectomy does not provide any advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Furthermore, patients undergoing sleeve resection may experience an improved postoperative quality of life compared to patients with a pneumonectomy which was described by Deslauriers et al [65] . Finally, a recent study by Schirren et al [66] showed even in patients with advanced nodal disease no significant advantage for pneumonectomy over sleeve resection.…”
Section: Bronchoplastic Lung Resectionmentioning
confidence: 95%
“…Furthermore, patients undergoing sleeve resection may experience an improved postoperative quality of life compared to patients with a pneumonectomy which was described by Deslauriers et al [65] . Finally, a recent study by Schirren et al [66] showed even in patients with advanced nodal disease no significant advantage for pneumonectomy over sleeve resection.…”
Section: Bronchoplastic Lung Resectionmentioning
confidence: 95%
“…47/57, ryc. 50), a niedawno opublikowano także kolejne, podobne znaleziska również z terenu Pomorza Przedniego (Schirren 2013). Obie wrocławskie odznaki najczęściej interpretuje się jako wizerunki orłów.…”
Section: Odznaki Heraldyczneunclassified